Highly emissive organic solids with remarkably broad color tunability based on N,C-chelate, four-coordinate organoborons - Shaikh, Aslam C.; Ranade, Dnyanesh S.; Thorat, Shridhar; Maity, Arunava; Kulkarni, Prasad P.; Gonnade, Rajesh G.; Munshi, Parthapratim; Patil, Nitin T. (Chemical Communications, 2015)
Molecular fluorophores based on N,C-chelate, four-coordinate organo-borons exhibit tunable solid-state emission colors that cover the whole visible region from blue to red. The emission color can be tuned through the substituents on either quinolines or the boron center.

Oxidative intramolecular 1,2-amino-oxygenation of alkynes under Au(I)/Au(III)-catalysis: discovery of pyridinium-oxazole dyad as novel lonic fluorophore - Shaikh, Aslam C.; Ranade, Dnyanesh S.; Rajamohanan, Pattuparambil R.; Kulkarni, Prasad P.; Patil, Nitin T. (Angewandte Chemie International Edition, 2016)

Oxidative intramolecular 1,2-amino-oxygenation of alkynes under Au-I/Au-III catalysis: discovery of a pyridinium-oxazole dyad as an ionic fluorophore - Shaikh, Aslam C.; Ranade, Dnyanesh S.; Rajamohanan, Pattuparambil R.; Kulkarni, Prasad P.; Patil, Nitin T. (Angewandte Chemie-International Edition, 2017)
Oxidative intramolecular 1,2-amino-oxygenation reactions, combining gold(I)/gold(III) catalysis, is reported. The reaction provides efficient access to a structurally unique ionic pyridinium-oxazole dyad with tunable emission wavelengths. The application of these fluorophores as potential biomarkers has been investigated.